COMPARATIVE ANALYSIS OF TRADITIONAL AND STUDENT-CENTERED METHODS IN TEACHING ENGLISH AS A FOREIGN LANGUAGE - Kurbanbaev Djavod Aminbaevich; Reymova Myassar Jen’isbaevna (International Journal of Literature and Language Studies, 2026)
Abstract: Teaching English as a Foreign Language (EFL) has undergone significant methodological changes over the past decades. Traditional teacher-centered methods, which emphasize grammar instruction, translation, and memorization, have gradually been complemented or replaced by student-centered approaches that focus on communication, interaction, and learner autonomy. This article presents a comparative analysis of traditional and student-centered methods in EFL teaching. The study examines their theoretical foundations, classroom practices, roles of teachers and learners, and impact on language skill development. Special attention is given to speaking, motivation, learner engagement, and communicative competence. The findings indicate that while traditional methods are effective for developing grammatical knowledge and reading comprehension, student-centered approaches are more successful in improving communicative skills and learner motivation. The article concludes that a balanced integration of both approaches can lead to more effective English language teaching in modern educational contexts.